Template-assisted preparation of imbricate N–MoxC nanotubes for the effective electrocatalytic hydrogen evolution reaction. Issue 11 (27th February 2023) - Li, Songjie; Su, Shilong; Tian, Yun; Li, Yuanyuan; Yu, Xiaomei; Sun, Panfei; Zheng, Jin You
Abstract : Imbricate N–Mo x C nanotubes with enlarged specific surface area achieve an excellent electrocatalytic performance for the alkaline hydrogen evolution reaction. Abstract : Molybdenum carbide (Mo2 C) has become a promising candidate for electrocatalytic hydrogen production from water splitting due to its low price and platinum-like electrocatalytic properties. In this work, Mo2 C nanotubes (Mo2 C NTs) with ultrathin imbricate structure were successfully synthesized by carburizing polydopamine organic layer covered molybdenum trioxide (MoO3 ) nanowire templates at elevated temperature through organic–inorganic hybridization. The inner diameter and wall thickness of the as-synthesized Mo2 C NTs are about 150 nm and 100 nm, respectively. Two-dimensional Mo2 C nanoflakes with a thickness of about 10 nm were composed of nanoclusters with a size of 2 nm. Furthermore, N–Mo x C was facilely prepared by nitrogen doping into the prepared Mo2 C by chemical vapor deposition and the enhanced electrocatalytic activity was obtained with an overpotential of 120 mV at a current density of 10 mA cm −2 . An enlarged specific surface area of 189 m 2 g −1 was achieved for N–Mo x C, which provides more electrocatalytic active sites for water reduction. More importantly, the interface optimization of Mo2 C and MoC was expected to modify the electronic structure and accelerate the electron transfer for improved water splitting performance.